2021
DOI: 10.3390/pharmaceutics13091400
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy with Fluoxetine and the Nucleoside Analog GS-441524 Exerts Synergistic Antiviral Effects against Different SARS-CoV-2 Variants In Vitro

Abstract: The ongoing SARS-CoV-2 pandemic requires efficient and safe antiviral treatment strategies. Drug repurposing represents a fast and low-cost approach to the development of new medical treatment options. The direct antiviral agent remdesivir has been reported to exert antiviral activity against SARS-CoV-2. Whereas remdesivir only has a very short half-life time and a bioactivation, which relies on pro-drug activating enzymes, its plasma metabolite GS-441524 can be activated through various kinases including the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 77 publications
2
68
0
Order By: Relevance
“…Re-analysis of data on amlodipine of previously published CCB retrospective studies is also suggested. Taking into account that there is some data for, firstly, the combination treatment in cells infected by SARS-CoV-2 with remdesivir or its predominant serum metabolite GS-441524 with fluoxetine [ 18 , 19 ], or secondly, the combination treatment in infected cells with remdesivir and diltiazem and another CCB [ 34 ], combination treatment using amlodipine with remdesivir could be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Re-analysis of data on amlodipine of previously published CCB retrospective studies is also suggested. Taking into account that there is some data for, firstly, the combination treatment in cells infected by SARS-CoV-2 with remdesivir or its predominant serum metabolite GS-441524 with fluoxetine [ 18 , 19 ], or secondly, the combination treatment in infected cells with remdesivir and diltiazem and another CCB [ 34 ], combination treatment using amlodipine with remdesivir could be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies have reported that fluoxetine inhibited the entry and propagation of SARS-CoV-2 in the cell culture model without cytotoxic effects [ 16 , 17 ], and two studies have found that combination therapy including fluoxetine exerts antiviral effects against SARS-CoV-2. The first study [ 18 ] reported that a combined treatment with fluoxetine and GS-441524, the principal serum metabolite of remdesivir, displayed antiviral effects against three SARS-CoV-2 variants in vitro. The second study [ 19 ] tested the fluoxetine–remdesivir combination on the SARS-CoV-2 replication in vitro and found impaired viral replication with combination treatment to be well-tolerated.…”
Section: Introductionmentioning
confidence: 99%
“…Targeting both the host and the virus should also be considered given the synergy of the combination of fluoxetine with direct-antiviral agents (e.g., remdesivir and its metabolite GS-441524) that has been displayed on ex vivo cellular models ( Brunotte et al, 2021 ; Schloer et al, 2021 ). Moreover, the combination of a host-directed drug (i.e., baricitinib) and of an antiviral (i.e., remdesivir) in patients hospitalized with moderate to severe disease for COVID-19 has been proven beneficial in reducing the recovery time, and in speeding up the improvement in clinical outcomes ( Kalil et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In September 2021 the Reschler group published a study [ 64 ] wherein they investigated the synergy of fluoxetine with the GS-441524 nucleoside analogue. GS-441524 is the main plasma metabolite of remdesivir with a plasma half-life of 24 h. Human data on GS-441524 are scarce, the current applications are mainly experimental and veterinary [ 65 ].…”
Section: Experimental Data That Support the Concept That Fluoxetine M...mentioning
confidence: 99%